2021
DOI: 10.1016/j.contraception.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraceptive use in Ghana: The role of method attributes and side effects in method choice and continuation

Abstract: Objective: To understand the barriers and facilitators of hormonal contraceptive use among Ghanaian women, in order to help improve contraceptive counseling and reduce the high rates of unintended pregnancy. Study design: We conducted a nationally representative community-based survey of 4143 women aged 15-49 in 2018, and used descriptive statistics and logistic regression to examine correlates of current hormonal method use, preferred method attributes and their association with method choice, and the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
3
19
0
1
Order By: Relevance
“…Prior analyses of these data showed that among all respondents aged 15-49 years in our sample who had ever had sex (n=4,139), 33.7% currently reported using any contraceptive method. 44…”
Section: Survey Design and Implementationmentioning
confidence: 99%
“…Prior analyses of these data showed that among all respondents aged 15-49 years in our sample who had ever had sex (n=4,139), 33.7% currently reported using any contraceptive method. 44…”
Section: Survey Design and Implementationmentioning
confidence: 99%
“…A major concern of using MCMs is side effects as has been established by several studies conducted in LMICs and sub-Saharan Africa [12,14,28].The experience of side effects resulted in discontinuation of MCMs, switching between MCMs or shifting to TCMs. Moreover, the fear of side effects as a result of the experiences of friends or close relatives was the reason for the nonuse of MCMs, as reported by studies in Ghana [29,30,31,32,10]. The reported side effects were headaches; dizziness; heart palpitations; and irregular, ceased or excessive menstruation.…”
Section: Summary Of Main Resultsmentioning
confidence: 89%
“…Young people’s preference for condoms and withdrawal over hormonal methods appears somewhat discrepant with their ranking effectiveness as their most valued method attribute. One explanation is inaccurate perceptions around the relative effectiveness of various contraceptive methods [ 37 ]. Alternatively, their method choices may be explained by other top attributes: no risk of harming health or future fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Data for this analysis come from a 2018 nationally representative household-based survey of Ghanaian women aged 15–49. Information on the study design and sampling plan are described in depth elsewhere [ 37 ]. Trained interviewers administered a structured questionnaire face-to-face in a private area using password-protected Android tablets enabled with Open Data Kit.…”
Section: Methodsmentioning
confidence: 99%